Regulación de entrada: Experiencia peruana sobre prohibiciones y restricciones para el acceso al mercado - Quintana Sánchez, Eduardo (2016)
This article addresses the way entry regulation works, creating prohibitions for the access of new competitors to markets (absolute effects) or limitations to the number of providers that can operate in the market (relative effects). The paper also assesses whether Peruvian legal framework allows for entry regulation, because it guarantees free private initiative and prohibits the creation of legal monopolies. Finally, several examples from Peruvian experience are used to explain the scenarios were entry regulation can have suitable and reasonable justification, as well as other scenarios were such measures lack support and cause negative effects on the market and consumer choices.